Human Dignity and Bioethics - Marjanović, Miloš (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
By opening the field of bioethics followed a new wave of intense debate on the theological, philosophical and legal significance of the concept of human dignity . Exactly ten years ago (December 2003) American bioethicist Ruth Maclin has proposed to divest ourselves of the concept of human dignity because it is vague, useless and redundant and that, without any loss, we can replace it by the ethical principle of personal autonomy. Her article was followed by harsh reactions and opposite views. What is this term in so broad, almost inflationary and opposite use is not a reason to deprive him, but, on the contrary, it shows how important it is and that it should be determined at least outline. As universal values ​​and general concept, the human dignity has no pre-defined and narrow, precise meaning. It is more an evaluation horizon, the guiding principle and regulatory ideas that must constantly define and codify by many guaranted human rights and fundamental freedoms. As generic notion of each reasonable law, it is their foundation and a common denominator, legitimising basis of natural but also of positive law. As  intrinsic and static value which means  the humaneness, the humanity it is absolute, inherent to every human being without distinction and conditioning, as a unique and unrepeatable creation. In this meaning, the dignity is the obligation and limitation of the state, society and each of us. As an ethical and dynamic category, it is not given to us, but it is assign to us, and it is not in  us, but always before us, as a guide of our actions in accordance with virtues, to treat ourselves, each other and the nature in a human way. The century in which we live is named the century of molecular biology and genetic engineering because of the enormous potential but also risks to human dignity. Because of that human dignity has become a central principle in all international documents relating to the human genome, genetics and bioethics, adopted by UNESCO and the Council of Europe, at the turn of the century, as well as in other documents that refer to them . Human dignity is the paradigm of our time. For more than half a century, it structures the rule of law, it is a constituent of a modern democratic society, announces a new, partnership with nature and creates a new image of every man as a hero of our time .
Keywords: declarations on the human genome; genetics and bioethics; generic concept of human rights and paradigm of our time; the central regulatory idea; human dignity as the horizon of the evaluation